PAY FOR PERFORMANCE : STUDI LITERATUR - Sawitri, Ana; Perdhana, Mirwan Surya (Faculty of Economics and Business Diponegoro University, 2018)
Pay for performance is one of financial compensation programs that aims to improve employee performance by offering more income based on result of employee performance appraisal. The purpose of this study is to present literature reviews on the perception of implementation and effectiveness of pay for performance program. Research method using systematic literature review. The research was conducted qualitatively by collecting 21 journals related to pay for performance. Various literature reviews of pay for performance were collected to get results on the implementation and effectiveness of pay for performance programs.The result shows that pay for performance program is effective to be implemented in order to increase the performance of employee and firm